Pathological Bases and Clinical Application of Long Noncoding RNAs in Cardiovascular Diseases. Issue 1 (1st June 2021) - Zhang, Chengxin; Niu, Kaiyuan; Lian, Panpan; Hu, Ying; Shuai, Ziqiang; Gao, Shan; Ge, Shenglin; Xu, Tao; Xiao, Qingzhong; Chen, Zhaolin
Abstract : Increasing evidence has suggested that noncoding RNAs (ncRNAs) have vital roles in cardiovascular tissue homeostasis and diseases. As a main subgroup of ncRNAs, long ncRNAs (lncRNAs) have been reported to play important roles in lipid metabolism, inflammation, vascular injury, and angiogenesis. They have also been implicated in many human diseases including atherosclerosis, arterial remodeling, hypertension, myocardial injury, cardiac remodeling, and heart failure. Importantly, it was reported that lncRNAs were dysregulated in the development and progression of cardiovascular diseases (CVDs). A variety of studies have demonstrated that lncRNAs could influence gene expression at transcription, post-transcription, translation, and post-translation level. Particularly, emerging evidence has confirmed that the crosstalk among lncRNAs, mRNA, and miRNAs is an important underlying regulatory mechanism of lncRNAs. Nevertheless, the biological functions and molecular mechanisms of lncRNAs in CVDs have not been fully explored yet. In this review, we will comprehensively summarize the main findings about lncRNAs and CVDs, highlighting the most recent discoveries in the field of lncRNAs and their pathophysiological functions in CVDs, with the aim of dissecting the intrinsic association between lncRNAs and common risk factors of CVDs including hypertension, high glucose, and high fat. Finally, the potential of lncRNAs functioning as the biomarkers, therapeutic targets, as well as specific diagnostic and prognostic indicators of CVDs will be discussed in this review.